A study on building maintenance at government school / Shudiani Mohd Sukri - Mohd Sukri, Shudiani (2006)
School is an educational institution and a building where young people receive education. A proper maintenance management is importance for school building to make sure the user of the building especially student can study in good condition. Most people are not aware of the important of maintenance management of public building especially schools. A school is basically the starting point in creating or develops a society or organization. Without a good management especially in school, it may have difficulty to produce the quality people in the society. The best maintenance is the kind that prevents problems from ever happening and actually can save school districts money and minimize disruptions in the education process. Preventive maintenance has got to be scheduled and has a guideline to make sure the maintenance works are operation smoothly.